TRENDS IN DEVELOPMENT OF LATE DEVONIAN REEFS - Kuznetsov V.G. (My University, 2002)
The Late Devonian was a period of degraded reef formation that was very intense in the Middle Paleozoic. Principal reef-building organisms, such as stromatoporoids, rugoses, and tabulates of the Frasnian Stage, were replaced by Famennian cyanobacteria and algae at that time. This resulted in development of Famennian frameless buildups instead of Frasnian framework reefs since the late Frasnian through the early Famennian. The difference in tectonic settings of reef development in continental and oceanic stratisphere segments is established. In oceanic segments, the frameless reefs were likely formed earlier than in continental settings.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская